The immediate effect of traditional Malay massage on substance P, inflammatory mediators, pain intensity and functional outcome among patients with low back pain: a pilot randomized-controlled trial / Nurhanisah Sejari - Sejari, Nurhanisah (2019)
Treatment of low back pain is very challenging due to the recurrent nature of the problem. It is believed that traditional Malay massage may help to relieve such back pain but there is a lack of scientific evidence to support both the practice of traditional Malay massage and the mechanism by which it exerts its effect. The aim of this thesis is to investigate the immediate effect of traditional Malay massage on substance P, inflammatory mediators, pain scale and functional outcomes among patients with low back pain. A pilot, non-blinded, randomized-controlled trial was conducted involving sixty patients who fulfilled the inclusion criteria. The participants were then randomly allocated into intervention (i.e. traditional Malay massage) and control (Le. relaxation position) groups.